Dual Metastability in Electroless Plating: Complex Inertness Enabling the Deposition of Composition‐Tunable Platinum Copper Alloy Nanostructures - Stohr, Tobias (Chemistry, 2020)
Autocatalytic deposition represents a facile, versatile, and scalable wet‐chemical tool for nanofabrication. However, the intricate component interplay in plating baths containing multiple metal species impedes alloy deposition. We resolved this challenge in the bimetallic copper‐platinum system by exploiting the kinetic stability of platinum complexes, which allows adjusting their ligand sphere and thus reactivity independently from the present copper ions in a preceding, thermally activated ligand exchange step. By using metastable Pt(IV) precursors of varying degrees of complexation, copper‐platinum alloys of adjustable atomic ratio were plated from solutions of identical composition and concentration, but differing local coordination environment. Due to its excellent conformity and nanoscale homogeneity, the reaction is compatible with ambitious 3D substrate morphologies, as demonstrated in the template‐assisted fabrication of nanotubes with high aspect ratio. The ability to generate additional synthetic degrees of freedom by decoupling the metal complex speciation from the solution composition is of large interest for redox‐chemical synthesis techniques, such as electrodeposition or nanoparticle colloid production.